Acoustic fields generation by plasmoids in the wellbores - Fedun, V.I.; Kolyada, Yu.E.; Bulanchuk, O.N. (Вопросы атомной науки и техники, 2013)
In this paper it is proposed a method of acoustic pulses generation in a wellbore by means a plasma gun which located at the well mouth. Acoustic measurements results are presented. It is shown that the wellhead pressure affects on the amplitude and hydrodynamic pulse shape, on its attenuation and the impact intensity at the wellbottom zone. It was determined the range of wellhead pressures at which a impulse force of wave reaches the highest values at the well bottom zone. It is shown that this method can favorably affect on the oil well productivity.